Effects Of Organic Substance And Plant Growth Regulators On Yield Attributes And Quality Of Guava Cv. Lucknow 49 - Dabhi, DM; Patel, Mj; Macwan, SJ (Bangladesh Journal of Botany, 2023)
In the present study effects of organic substance and plant growth regulators on yield attributes and quality of guava cv. Lucknow 49 were conducted during 2021-2022. Results indicated that foliar application of novel organic liquid fertilizer (40 ml/l) gave higher yield parameters viz. number of flowers per branch, fruit set, weight per fruit, fruit volume, fruit diameter, fruit length, pulp weight per fruit, number of fruits per plant, fruit yield (kg/plant) during both the years and in pooled data. In quality parameters, higher chlorophyll content and pulp: seed ratio were recorded with novel organic liquid fertilizer (40 ml/l) during both the years and in pooled data. However, organic substance and plant growth regulators treatments showed non-significant effect on total seed weight per fruit in both the years as well as in pooled data. Bangladesh J. Bot. 52(4): 971-978, 2023 (December)